The Evaluation of Inclusive Education Programs in Two Primary Schools in Sidoarjo - Liswandari, Ajeng Linda; Hariyati, Nunuk; Khamidi, Amrozi (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to determine the implementation of inclusive schools in Sidoarjo Regency. The schools are SD Negeri Sidokerto and SD Muhammadiyah 2 Tulangan. This research describes the system, human resources and learning outcomes of students with disabilities through the CIPP or Context, Input, Process, and Product evaluation model. A descriptive phenomenological approach was used to obtain data on implementing inclusive schools. The research was aimed at the 5th-grade elementary school level and was supported by interaction with GPK students with disabilities or shadow teachers, class teachers, and school principals. Interaction is carried out by observing classes and supporting activities at school, as well as in-depth interviews and documentation to support the data. Data analysis in this research uses the theory of Miles and Huberman to clarify the results of interactions at the 5th-grade level in each school. Thus, the study results show a comprehensive path by knowing that students with disabilities at the two schools can compete and have adequate competencies in academic and non-academic fields and that the schools are worthy of providing inclusion. However, this inclusive school management program requires special supervision that explicitly integrates developments and natural conditions in meeting school needs.